Lannan kestävä hyödyntäminen - Luostarinen, Sari (toim.); Logrén, Johanna (toim.); Grönroos, Juha (toim.); Lehtonen, Heikki (toim.); Paavola, Teija (toim.); Rankinen, Katri (toim.); Rintala, Jukka (toim.); Salo, Tapio (toim.); Ylivainio, Kari (toim.); Järvenpää, Markku (toim.) (MTT, 2011)
HYÖTYLANTA-tutkimusohjelmassa tuotettiin työkaluja lannan ja muiden eloperäisten jätteiden ja sivutuotteiden hallintaan, erityisesti niiden sisältämien ravinteiden kierrättämiseksi ja energiasisällön hyödyntämiseksi taloudellisesti ja ympäristöllisesti kestävällä tavalla. Hankkeessa tutkittiin mahdollisuuksia lantaravinteiden tehokkaampaan käyttöön, lannan ja muiden eloperäisten materiaalien prosessointivaihtoehtoja sekä eri teknologioiden soveltamisen taloudellisia vaikutuksia. Lisäksi arvioitiin eri lannankäsittelyvaihtoehtojen elinkaariset ympäristövaikutukset ja vaihtoehtojen kokonaiskestävyys. Lannan ravinnesisältöön ja ravinteiden liukoisuuteen voidaan vaikuttaa jo eläinten ruokintavaiheessa säätämällä rehuannoksen fosforin ja typen määrää ja laatua (eläimen tuotantovaiheen mukainen ruokinta sioilla ja siipikarjalla) ja parantamalla rehun fosforin hyväksikäyttöä fytaasientsyymillä. Lannan prosessointi vaikuttaa ravinteiden käyttökelpoisuuteen kasveille. Orgaanisista lannoitevalmisteista nestemäiset ja lantapohjaiset jakeet ovat typpipitoisuudeltaan korkeimpia ja kuivajakeet yleensä matalimpia, erityisesti kasveille käyttökelpoisen typen osalta. Lannan jakeistamisella tai rakeistuksella voidaan nostaa kuivajakeen fosforipitoisuutta, mutta samalla typpipitoisuus alenee ja haitallisten metallien pitoisuudet nousevat. Keskeinen ongelma lannan hyödyntämisessä on erityisesti lietelannan korkea fosforipitoisuus fosforilannoitustarpeeseen nähden. Ongelman ratkaisu edellyttää jakeistusteknologioiden käyttöä etenkin tiloilla, joilla lantaa syntyy monin verroin suhteessa fosforilannoitustarpeeseen. Kiintoaineen ja sen sisältämän fosforin erottaminen lietelannasta säästää levityskustannuksia ja helpottaa typpipitoisen nestejakeen hyödyntämistä tilan lähipelloilla. Tulosten mukaan heikommankin fosforinerotustehon tekniikka saattaa olla tiloille taloudellisesti kannattava vaihtoehto. Yksittäisten kotieläintilojen mahdollisuudet investoida lannankäsittelyteknologioihin ovat vähäiset, mutta jo 2-3 suuren tilan yhteisinvestoinnit voivat olla kannattavia. Tehokkaamman lannan käytön vuosihyödyt voivat olla maataloudelle noin 10 miljoonan euron luokkaa. Epäorgaanisen lannoitefosforin vähen-tämispotentiaali on jopa 30-50 %, jos lannan fosfori voidaan alueellisesti kohdentaa sen tarvetta vastaavasti. Jakeistaminen sopii hyvin yhteen sijoituslevityksen kanssa sekä biokaasutuotannon kanssa. Lannankäsittelyvaihtoehtojen taloudelliset vaikutukset osoittautuivat pieniksi suhteessa tilojen liikevaihtoon ja maatalouden kokonaistuotantoon. Hankkeessa tehdyn ympäristövaikutusten arvioinnin perusteella biomateriaalien käsittelyn ja hyötykäytön ympäristövaikutukset johtuvat eri vaikutusluokissa 75-90 % lannasta esimerkkialueena toimineessa Satakunnassa. Päästötekijöistä selvästi merkittävin on rehevöitymistä, happamoitumista ja hiukkaspäästöjä aiheuttava ammoniakki, jonka päästöjä vähentämällä myös kokonaisympäristövaikutuksia voidaan vähentää eniten. Ilmastonmuutosvaikutus osoittautui hyvin pieneksi, joten lannan kuljetus huomattavasti nykyistä kauemmas on perusteltua, mikäli sillä saavutetaan hyötyä esimerkiksi vesiensuojelun kannalta. Tutkimuksen suositusten mukaan lantavarastot tulisi kattaa ja suosia lannan sijoituslevitystä typpihävikin minimoimiseksi. Ympäristönäkökulmasta lannan ja lannoitevalmisteiden syyslevitystä ilman kasvuston perustamista tulisi välttää, erityisesti vesistöjen lähellä. Lannan fosforinkäyttöpoikkeuksista tulisi asteittain luopua ja uusien ympäristölupien perustua poikkeuksettomiin fosforinkäyttömäärin. Lannan jakeistusmenetelmien käyttöönottoa tulisi suosia erityisesti alueilla, joilla kotieläintiheys on suuri. Ravinteiden ja energian yhteistuotannon tehostamiseksi prosessien hyötysuhteita tulisi parantaa ja päästöjä vähentää kaikissa tuotannon vaiheissa.

In Finland, agriculture accounts for 60% of total phosphorus and 52% of nitrogen load to waterbodies as generated by human activity. The Finnish animal husbandry produces annually approximately 20 million tonnes of manure. In addition, around 840,000 tonnes of sewage sludge is generated each year. Finnish farms are small on a European scale, but the unit size of animal husbandry is growing. Regional concentration of animal husbandry and the increasing size of production units are also causing regional and local concentration of manure. The need to exploit the nutrients and energy contained in manure more efficiently has grown simultaneously with regional environmental hazards from manure, such as nutrient runoff, eutrophication and undesirable odours. Moreover, integrated processing with other organic materials offers the possibility of managing and exploiting their nutrient and energy content and relieving the burden on the environment. A study requested by Finland's Ministry of Agriculture and Forestry ("Research programme to discover reuse options for manure and other organic wastes and by-products, HYÖTYLANTA") offered tools for managing manure and other organic materials in order to recycle their nutritional content and exploit their energy content in a financially and environmentally sustainable manner. The research programme was divided thematically into four sections, as follows: 1. Developing the use of manure as fertiliser, and efficient use of nutrients 2. Processing manure and other organic wastes and by-products 3. Assessment of the economic impact of manure use at the farm and regional level 4. Life cycle analysis of the environmental impact of manure processing, and assessment of the overall sustainability of alternative treatments The research was coordinated by MTT Agrifood Research Finland, and other participating organisations were Finnish Environment Institute (SYKE), Department of Agricultural Sciences at University of Helsinki, Työtehoseura, and the Association of Pro Agria Centres. Developing the use of manure as fertiliser, and efficient use of nutrients In order to identify ways for developing manure use as fertiliser, the following matters were studied: i) the effect of animal feeding and manure processing on the solubility and amount of phosphorus in manure; ii) optimisation of phosphorus at farm level; iii) the possibilities for minimising harmful effects of phosphorus surface application, and iv) the impact of organic nitrogen from manure and processed products. The nutrient content of manure and solubility of nutrients can be affected already in animal feeding by adjusting the amount and quality of phosphorus and nitrogen in feed (e.g. phytase additive and feeding of animals according to their stage of g rowth with pigs and poultry). The amount of phosphorus in feeding has been measured in a new Finnish study (MTT 2010). In practice, there is no need for mineral phosphorus when feeding dairy cows. When mixing feeds, the phosphorus content of the basic feed should also be taken into account, so that several phosphorus-rich raw ingredients are not unnecessarily added to the mix. The proportion of water-soluble phosphorus in total phosphorus increases when the phosphorus density of feed is lowered by reducing the use of inorganic phosphate. Replacement of phosphate with phytase may slightly increase the proportion of water-soluble phosphorus in manure, which causes a reduction in the use of inorganic phosphate fertiliser. The proportion of water-soluble phosphorus decreases when the ratio of calcium to phosphorus rises. The Ca:P -ratio of pig feed normally varies between 1.1-1.6:1. The phosphorus in pig manure is more easily soluble in water when grain-based by-product feeds are used in comparison to grain-based feed. However, increasing the fibre-density of barley protein feed by subjecting part of the grain's fibre fraction to distillation reduces the solubility of manure phosphorus. The effect of reducing phosphorus fertiliser on the phosphorus density of grains is not known with any accuracy, but it is not profitable to keep the phosphorous density of kernels high through fertilisation, rather optimisation is most effective using phosphate and/or phytase additives. Nutrient solubility may change as a result of manure processing. The solubility of nitrogen and other nutrients generally increases during processing. On the other hand, when treating several raw materials together, changes in nutrient solubility may be different, as indicated by decreased proportion of water-soluble phosphorus in relation to total phosphorus when co-digesting liquid cow manure and grass silage. The phosphorus content of pelletised organic fertiliser product (produced from digested pig manure and industrial by-products) was 2-3% at maximum (0.3-1% when fresh) and the proportion of water-soluble phosphorus in total phosphorus was as low as under 1%. The phosphorus content of organic soil improver is important if the field requires phosphorus fertilisation. Mechanical separation or pelletising may be used to increase phosphorus content, but at the same time nitrogen concentration decreases and the concentration of hazardous metals may rise. The nitrogen fertiliser effect of manure is affected by its ammonium nitrogen content, ammonia evaporation and runoff risks elevated by autumn application. The limitations on total nitrogen use (N 170 kg/ha) and the strategy in phosphorus fertilisation affect the amount of manure-based products used and the applicability of nitrogen fertiliser. The nitrogen fertiliser impact of horse manure depended on bedding material: peat produced a fertiliser effect in line with soluble nitrogen content, whereas sawdust consumed both the soluble nitrogen in horse manure and the soluble nitrogen in the soil as it decomposed. The release of organic nitrogen from manure is slow and occurs as a function of soil temperature and humidity, which does not necessarily correspond to the nitrogen requirements of crops. The impact of organic nitrogen is only observed following the annual application, and in plants that absorb nitrogen over their entire growth cycle. The nitrogen proportions of manure-based organic fertiliser products vary considerably according to raw materials and processing technology. The liquid organic fertiliser products contain more nitrogen, while the dry products generally contain less nitrogen. The reuse of nutrients and organic material in agriculture is the only sustainable solution. The cadmium limit in several organic fertiliser products (Cd 1.5 g /ha/a) can reduce the amounts applicable and limit use on the same filed plots at four-year intervals (max 6 g Cd/ha per four years). The volumes of recycled materials in Finland are significant in relation to their possibilities for field application. The soluble nitrogen in a product does not necessarily cover the cost of application, but on field plots requiring phosphorus and as reused phosphorus their use is beneficial. Processing of manure and other organic wastes and by-products The use of manure as fertiliser is weakened by the unfavourable N:P ratio of manure, the properties and relatively low concentrations of nutrients, and greater difficulty of application than with mineral fertilisers. The basic problem with exploiting manure nutrients is the low nitrogen concentration in relation to phosphorus. Processing may relieve some of these challenges via production of more feasible organic fertiliser products. Processing may also affect the nutrient and greenhouse gas emissions from use and storage of manure and other organic wastes. In addition, manure energy potential can be exploited, or it can be used to promote the use of arable land as a carbon sink or reservoir. The present study examined manure processing technologies and technology chains applied on three different scales, which were farm scale, farm cooperative scale and centralised scale (co-treatment of manure and other organic wastes). Cattle and pig farms were used as example farms, with a standard farm producing 3,000 t/a of manure. Of the technologies, special attention was paid to manure separation into solid and liquid fractions and to biogas process. The ability of mechanical separation methods to separate solids and nutrients varies considerably, as do their investment costs. By using a decanter centrifuge or a screw press, a higher solid density is achieved than with a sieve separator, whereas the decanter centrifuge is best able to separate phosphorus. The cost of investing in the equipment with the best separation capacity is considerable, increasing the difficulty of making profitable investments in farm cooperatives. Technology with weaker phosphorus separation may be more financially viable in Finnish conditions, especially on cattle farms. Exploiting the energy potential of manure is possible with the help of e.g. biogas technology. A biogas plant produces a gross annual energy yield of 320-330 MWh/a from the liquid manure of one standard-sized farm. The addition of grass silage (300 t/a) together with manure doubles the gross energy production of a standard farm, and the nutrients in the digestate meet the fertilisation needs of plants. A shared biogas plant of five farms (farm cooperative) can use the liquid manure of one farm as such, and the separated solid fraction of the four other farms (screw decanter). Further separation of the digestate produces an extremely phosphorus-rich solid fraction and a liquid fraction with little phosphorus. If solely dry fractions were to be digested, the feed must be diluted, and a considerable amount of methane potential is lost. The centralised treatment of manure (10 farms + 30,000 tonnes of other biomaterial) in a biogas plant results in the production of a classified organic fertiliser product. In this case, the application surface area required must take into account total nitrogen, soluble nitrogen and water-soluble phosphorus according to official analysis made or, in plants digesting sewage sludge, 40% of total phosphorus (cf. 85% of total phosphorus in manure installations). Centralised biogas plants may also use several different post-processing techniques to produce targeted fertiliser products. The energy used at the plant and the nutrient content and ratios of the end-products are fundamentally affected by the raw materials. From the perspective of nutrient use of crops, nitrogen content and solubility of the end-products are of key importance. The effective and economical operation for biogas plants as a rule requires efficient use of the biogas energy content (CHP, transport fuel) as well as the use of manure and other organic materials, such as plant biomass. Maximising the environmental benefits of processing requires minimisation of emissions in each process of the technology chain. The development of processing technologies for fertiliser products should also be examined in terms of market needs. The production of targeted fertiliser products for the market, and their removal to regions in need of fertilising requires financial incentives for the development of processing technologies and their implementation on all scales. Assessment of the economic impact of manure use at the farm and regional level The productisation of manure will have an impact on the conditions and competitiveness of animal husbandry. Over the long term, changes in the structure of animal husbandry may in turn have broader effects on regional economies. Growth in the size of animal farms will increase the amount of manure per farm and per hectare, but the processing technologies may enable transportation of manure nutrients over broader area, which would enhance the ability of animal farms to increase the number of animals without increasing field area. The research on economy estimated how production arrangements aimed at manure and other organic materials (e.g. separation of phosphorus from manure, production of biogas) affect the conditions and profitability of animal farms and in turn affect the structural development of agriculture, regional economies and employment. An examination of changes in the agricultural sector made use of the DREMFIA model developed at MTT, and the regional economic examination relied on the input-output model. In addition, several calculation tools were developed based on farm models, and they can be used to compare the profitability of different manure treatment and fertilisation alternatives. Separating liquid manure into phosphorus-rich solid fraction facilitates field application of the nitrogen-rich liquid fraction as such with improved absorption in the soil and reduced hygiene risk of manure microbes remaining on crops. Liquid fraction can be applied in larger quantities per hectare than raw manure due to its lower phosphorus content as regulated by environmental subsidies. In the best case, the need for nitrogen fertilisation can be met completely with manure nitrogen. At the same time, the transportation needs of manure can be decreased to less than half. Injection of liquid manure and/or liquid fraction of manure into soil also improves nitrogen exploitation and the profitability of separation, promoting the circulation of manure nutrients within farms. Separation of solids and phosphorus from manure offers - at least in principle - the possibility of recycling phosphorus, providing both a cost-effective procedure for transporting and applying the separated solid fraction on fields requiring phosphorus fertilisation is identified. The results show that high separation efficiency is not always the most important factor - particularly in areas dominated by dairy cows and cattle. A sufficient proportion of the excess phosphorus from animal dense areas can be separated using devices with medium or even weak separation efficiency, if it can be gathered and applied on fields requiring phosphorus at moderate expense. The study indicates that it may not pay to invest in manure separation devices on individual farms in Finland at the moment, but joint investments of 2-3 larger farms could be profitable. In order for investments to pay for themselves in the form of cost savings, the key thing is identifying a suitable distribution of labour and achieving sufficiently widespread activity. The study estimated that the annual benefits of more efficient manure use could be in the area of 10 million euros in the Finnish agriculture. The potential for reducing mineral phosphorus is as much as 30-50% if the phosphorus in manure can be targeted according to need. Processing which enhances manure use should be promoted first and foremost on larger farms and in regions of intense animal husbandry. Effective use of separation devices should be pursued in animal-dense regions using e.g. contracting and machinery rings. The important thing is to identify operating modes with which farms can together pursue profitable recycling of manure nutrients and share capital costs and risks. Particular effort should be made to ensure the overall benefit of crop farms receiving manure nutrients - not only the price of manure nutrients, but also the practical approach and distribution of labour should be competitive with respect to inorganic mineral fertilisers. There should also be certainty about the nutritional concentrations of manure to be applied on fields. Life cycle analysis of the environmental impact of manure processing, and assessment of the overall sustainability of alternative treatments Life cycle assessment (LCA) was used to study the effects of alternative manure management and processing on the environment. In addition, the overall sustainability (economic and social sustainability, environmental, health and safety aspects) of alternative biomaterials (residues from crop production and food production, sewage sludge) was assessed with the help of a so-called value tree analysis. Manure has a considerable environmental impact, since large masses, relatively significant nutrient content and multi-stage treatment are all typical of it. The majority of the environmental effects resulting from the treatment and utilisation of the biomaterials studied are caused precisely by manure. The formation of the overall environmental effects is in turn primarily affected by evaporating ammonia, because it causes eutrophication of soil and water environment, acidification, and the formation of particulates. By reducing ammonia emissions, the overall environmental effects of manure can also be further reduced. Annually, nitrogen runoff into waterbodies from manure application is a bigger problem in Finland than phosphorus runoff. The problem of excess phosphorus is a result of the high level of fertilisation in previous years and decades, which elevated the concentration of easily soluble phosphorus in field soil. Manure nitrogen is especially prone to wash away with autumn application at the end of the growing season. By optimising the use of manure as fertiliser, the risk of runoff can be minimised. At the same time, the use of mineral fertilisers, and with it the nutrient runoff caused by fertilisers and the emissions generated during manufacture of fertilisers, can be reduced. In animal housing, nitrogen loss can be reduced for example by removing manure more frequently, quickly separating urine into a separate urine container, and cooling manure channels. Emissions during storage are reduced by tightly covering manure stores. Gaseous nitrogen losses that occur during and after application on fields can be reduced most effectively by favouring the injection of manure, or if manure is applied on surface, it should be e.g. ploughed into soil as quickly as possible. In the overall environmental impact of processing and reuse of biomaterials, the significance to climate change was shown to be very moderate. The reason for this was that the overall impact of methane and dinitrogen oxide released from manure and other biomaterials and of carbon dioxide emissions was small in relation to the overall regional or national climate impact. Also, transportation of manure across farther distances than now is justified if it allows other environmental benefits. In Finland's current environmental subsidy system for agriculture, phosphorus and nitrogen from cattle manure are not entirely taken into account when calculating the amount of fertiliser that complies with conditions. 85 per cent of manure's soluble phosphorus is taken into account, and in autumn application 75 per cent of nitrogen. As a result of the present evaluations, spring and summer application of manure should be favoured and the application methods are to be developed in order to give up autumn application altogether. If manure is applied in autumn, the principle should be that due to environmental reasons 100% of nitrogen is taken into account during the following year. Moreover, usability of manure phosphorus is to be increased to 100% as the renouncement of exceptions to manure phosphorus would lead to reduction in phosphorus levels in field soils. Fertilisation with manure should always be based on the phosphorus condition of the field, even if it means longer transportation routes for manure. In connection, manure separation is also recom-mended to minimise transportation needs.
Keywords: Ka; Ys; LCA; orgaaniset lannoitteet; jakeistus; lanta; eloperäiset lannoitteet; ravinteet; elinkaarianalyysi; biokaasu; farmyard manure; organic fertilizers; nutrients; life cycle analysis; biogas; manure; fractionation